Galician Stage Design in the 21st Century - González Valeiras, Diego (Madrygal. Revista de Estudios Gallegos, 2015)
This article aims to make an analytic overview of the Galician stage design in the early twenty-first century and the relationship established both with the past as with different theatrical productions. The work of renown artists with a more classical style will be compared to the aesthetic and formal changes of new creators and how the later help the renovation of scenic modeling and its relationship with the public.